Ni–Zn bimetal-organic framework nanoprobes reinforced polymeric coating to achieve dual-responsive warning of coating damage and interfacial corrosion - Dezhi Jiao; Chengbao Liu; Yujie Qiang; Shuoqi Li; Cong Sun; Peimin Hou; Lanyue Cui; Rongchang Zeng (Nano Materials Science)
Coating microdefects and localized corrosion in coating/metal system are inevitable, accelerating the degradation of metal infrastructure. Early evaluating coating microdefects and detecting corrosion sites are urgent yet remain challenge to achieve. Herein, we propose a robust, universal and efficient fluorescence-based strategy for hierarchical warning of coating damage and metal corrosion by introducing the concepts of damage-induced fluorescence enhancement effect (DIE) and ionic-recognition induced quenching effect (RIQ). The coatings with dual-responsiveness for coating defect and steel corrosion are constructed by incorporating synthesized nanoprobes composed of metal organic frameworks (Ni–Zn-MOFs) loaded with Rhodamine B (RhB@MOFs). The initial damage to the coating causes an immediate intensification of fluorescence, while the specific ionic-recognition characteristic of RhB with Fe3+ results in an evident fluorescence quenching, enabling the detection of coating damage and corrosion. Importantly, this nanoprobes are insensitive to the coating matrix and exhibit stable corrosion warning capability across various coating systems. Meanwhile, electrochemical investigations indicate that the impedance values of RM/EP maintain above 108 ​Ω ​cm2 even after 60 days of immersion. Therefore, the incorporation of fluorescent nanoprobes greatly inhibits the intrusion of electrolytes into polymer and improves the corrosion protection performance of the coating. This powerful strategy towards dual-level damage warning provides insights for the development of long-term smart protective materials.